Implementasi Program UPTD Layanan Disabilitas dan Pendidikan Inklusif Kota Padang dalam Pemenuhan Hak Anak Berkebutuhan Khusus - Marni, Sistri; Suryanef, Suryanef; Isnarmi, Isnarmi; Fatmariza, Fatmariza (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2024)
This research aims to look at the implementation of programs related to fulfilling the rights of children with special needs carried out by the Regional Technical Implementation Unit for Disability Services and Inclusive Education (UPTD LDPI) Padang City. This research also looks at factors that hinder the fulfillment of the rights of children with special needs. The research method used is descriptive qualitative. The informants for this research consisted of: Head and staff of UPTD LDPI and parents of children with special needs. The data collection techniques used were observation, interviews and documentation studies. The data analysis technique is carried out in the stages of data collection, data reduction, data presentation, drawing conclusions. The research results show that the implementation of service programs for children with special needs has been carried out well. The inhibiting factors in fulfilling children's rights are: human resources, namely personnel/staff, parents and facilities and infrastructure. This is due to society's perception that children with special needs are still seen as a burden rather than serving and fulfilling their needs.